การนำบทบัญญัติเกี่ยวกับการบังคับขายหุ้นจากผู้ถือหุ้นรายย่อย (Squeeze Out) มาใช้ในประเทศไทย - อิสริยา วิมลรัตน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
At present, Thai law provisions in relation to the merger and acquisition in Thailand is insufficient to provide fairness and optimal benefit to all relevant parties in the event that the minority shareholders hold not exceeding 10 per cent of the total issued shares of the company. It is therefore necessary to conduct research on the squeeze out provisions adopted by a number of foreign countries to solve this problem so that the appropriate measure could be explored to solve such problem in Thailand. The research has been conducted by studying the squeeze out provisions adopted by the United States of America and the United Kingdom including the implications arising from the adoption of the squeeze out provisions as well as the court decisions in relation thereof in those countries which would be the basis for the adoption of the squeeze out concept in Thailand. The outcome of the research shows that the adoption of the squeeze out concept in Thailand would not only provide the fair and lawfully measures for the business acquirer to achieve its purpose of acquiring the total number of issued shares in the company but also protect the minority shareholders from the abuse due to the lack of the bargaining power. Consequently, it is appropriate that the squeeze out concept would be adopted in Thailand by introducing it as part of the Securities and Exchange Act B.E. 2535